A practical guide for collecting farmers socio-economic and agronomic data: an AfSIS Project field protocol - Okoth, Peter F.; Nambiro, E; Kibe, P; Njoroge, S; Macharia, R.; Kihara, Job Maguta; Huising, Jeroen (International Center for Tropical Agriculture, 2012)
One of the aims of the AfSIS (Africa Soil Information Service) project is to document farmers’ characteristics and practices to determine their ability to engage in effective soil and crop management. This document outlines how agronomic surveys are integrated with knowledge of farmers’ condition, wealth, status, access to knowledge, and access to markets, using pre-designed questionnaires and field surveys, and including the use of Global Positioning System-based field surveys and Geographic Information Systems.